PENGARUH GOOD CORPORATE GOVERNANCE DAN KEBIJAKAN MANAJEMEN CSR TERHADAP PROFITABILITAS DI INDEKS SAHAM SYARIAH INDONESIA - Marina, Nisha; Muhammd Ridha Habibi; Abdul Fatah Hassanudin; Nurjaman; Anggriyani (Jurnal Investasi, 2022)
The purpose of this study is to analyze whether good corporate governance and corporate social responsibility can affect the level of company profitability. Which is where GCG is proxied by managerial ownership, institutional ownership, and the independence of the Board of Commissioners. CSR is proxied using the Global Reporting Initiative (GRI) G-4 indicator with 91 assessment indicators, which consist of 9 points of economic performance assessment, 34 points of environmental performance assessment, 16 points of assessment of labor practices and work comfort, 12 points of human rights assessment. people, 11 points for community assessment, and 9 points for product performance assessment. This study uses data on the financial statements of companies in the consumer goods industry listed on the Indonesia Stock Exchange Sharia Stock Index (ISSI) for the period 2017-2020. The population in this study includes all companies in the consumer goods industry listed on the Indonesia Stock Exchange as many as 41 companies. The data collection method used in this research is purposive sampling. The sample in this study were 14 companies with an observation period of 4 years so that a total of 56 companies were observed. The conclusion of this study shows that good corporate governance does not partially affect the company's profitability. Corporate social responsibility partially affects the company's profitability. And good corporate governance and corporate social responsibility simultaneously affect the company's profitability.